Composite CYP3A phenotypes influence tacrolimus dose-adjusted concentration in lung transplant recipients. Issue 5 (7th April 2022) - Liu, Michelle; Shaver, Ciara M.; Birdwell, Kelly A.; Heeney, Stephanie A.; Shaffer, Christian M.; Van Driest, Sara L.
Abstract : Objectives: Interpatient variability in tacrolimus pharmacokinetics is attributed to metabolism by cytochrome P-450 3A4/5 isoenzymes (encoded by CYP3A4 and CYP3A5 ). Guidelines for adjusting tacrolimus based on CYP3A5 test results are published; however, CYP3A4 variants also contribute to the variability in tacrolimus pharmacokinetics. The effects of composite phenotypes incorporating CYP3A5 and CYP3A4 increased ( *1G, *1B ) and decreased ( *22 ) function variants have not been evaluated. The objective of this study is to investigate the impact of both increased and decreased function CYP3A variants on weight and dose-adjusted tacrolimus concentration (C0/D). Methods: We performed a single-center retrospective cohort study of lung transplant recipients to evaluate the median tacrolimus C0/D by composite CYP3A phenotype groups during the index transplant hospitalization. CYP3A4 and CYP3A5 alleles were used to classify patients into four CYP3A groups from least to most CYP3A activity. Exploratory analyses of ABCB1 and additional candidate genes were also assessed. Results: Of the 92 included individuals, most (58) were CYP3A Group 2. The median tacrolimus C0/D differed significantly between CYP3A groups ( P = 0.0001). CYP3A Group 2 median tacrolimus C0/D was 190.5 (interquartile range: 147.6–267.5) (ng/ml)/(mg/kg/d) and significantly higher than Group 4 [107.9 (90.4–116.1), P = 0.0001)]. Group 2 median tacrolimus C0/D did not significantly differ from Group 1 and Group 3 [373.5 (149.2–490.3) and 81.4 (62.6–184.1), respectively]. No significant differences in tacrolimus C0/D were found for the ABCB1 diplotypes. Conclusion: These data indicate that a composite CYP3A phenotype incorporating both increase and decrease variant information from CYP3A4 in addition to CYP3A5 may significantly influence tacrolimus C0/D during the early postoperative period.